The association of cognitive impairment with quality of life and functional impairment in Ugandan frst-episode psychosis patients: a cross sectional study - Mwesiga, Emmanuel K.; Ssemata, Andrew S.; Gumikiriza, Joy; Nanteza, Angel; Nakitende, Anne Jacqueline; Nakku, Juliet; Akena, Dickens; Nakasujja, Noeline (Health and Quality of Life Outcomes, 2022)
Cognitive impairment is common in first-episode psychosis patients and often associated with poor quality of life and functional impairment. However, most literature on this association is from high income countries and not low resource countries like Uganda. We aimed to determine the association between cognitive impairment with quality of life and functional impairment in Ugandan first-episode psychosis patients.
Keywords: cognitive impairment; life; psychosis patients